Recalcitrant chronic bladder pain and recurrent cystitis but negative urinalysis: What should we do? - Swamy, Sheela (Int Urogynecol J, 2018)
PURPOSE: Lower urinary tract symptoms (LUTS) may be associated with chronic urinary tract infection (UTI) undetected by routine diagnostic tests. Antimicrobial therapy might confer benefit for these patients. MATERIALS AND METHODS: Over 10 years, we treated patients with chronic LUTS. Pyuria was adopted as the principal biomarker of infection. Urinary leucocyte counts were recorded from microscopy of fresh midstream urine (MSU) samples. Antibiotics were prescribed and the prescription adjusted to achieve a measurable clinical response and a reduction in pyuria. RESULTS: We treated 624 women [mean age = 53.4 years; standard deviation (SD) = 18] with chronic LUTS and pyuria. Mean duration of symptoms prior to presentation was 6.5 years. Only 16% of MSU cultures submitted were positive (≥10(5) cfu ml(-1)). Mean treatment length was 383 days [SD = 347; 95% confidence interval (CI) = 337–428]. Treatment was associated with a reduction in total LUTS (F = 98; p = 0.0001), 24-h frequency (F = 75; p = 0.0001), urinary urgency (F = 90; p = 0.0001), lower urinary tract pain (F = 108; p = 0.0001), voiding symptoms (F = 10; p = 0.002), and pyuria (F = 15.4; p = 0.0001). Full-dose first-generation antibiotics for UTI, such as cefalexin, nitrofurantoin, or trimethoprim, were combined with methenamine hippurate. We recorded 475 adverse events (AEs) during 273,762 treatment days. There was only one serious adverse event (SAE). We observed no increase in the proportion of resistant bacterial isolates. CONCLUSION: This large case series demonstrates that patients with chronic LUTS and pyuria experience symptom regression and a reduction in urinary tract inflammation associated with antimicrobial therapy. Disease regression was achieved with a low frequency of AEs. These results provide preliminary data to inform a future randomized controlled trial (RCT).